The Effective Application of Concept Mapping in Marketing Education - Leung, Chi Hong; Cheng, Simone Chung Ling (Asian Journal of Empirical Research, 2018)
A concept map represents knowledge hierarchically. Concept mapping facilitates meaningful learning because it helps to 1) identify understanding, misconceptions, conceptual change, 2) facilitate collaboration and cooperative learning, 3) assess learning of students, and 4) organize and present information. This paper proposes a number of teaching and learning activities with concept mapping. After they were implemented in two marketing classes in a university, both the survey and quiz were used to verify its effectiveness. In the survey, 162 students had positive attitudes to concept mapping with the grand mean of 4.1 in the Likert scale from 1 (strongly disagree) to 5 (strongly agree). The quiz results (with the full mark = 30) also showed that there was academic improvement in two classes with the average scores changing from 17.5 to 24.3 and from 16.5 to 24.5 respectively. These positively proved that concept maps could facilitate teaching and learning activities and improve students’ academic performance significantly.